Cover Image: The infectious propagules of Aspergillus fumigatus are coated with antimicrobial peptides (Cellular Microbiology 03/2021). (10th February 2021) - Dümig, Michaela; Binder, Jasmin; Gaculenko, Anastasia; Daul, Franziska; Winandy, Lex; Hasenberg, Mike; Gunzer, Matthias; Fischer, Reinhard; Künzler, Markus; Krappmann, Sven
Abstract : Conidiophore of A. fumigatus carrying asexual spores that are coated with GFP as expressed from the defensin‐like peptide‐encoding defX gene. For further details, readers are referred to the article by Dümig et al. on p. e13301 of this issue.